Treating advanced kidney cancer—miles to go before we sleep - Linehan, W. Marston (2013)
A randomized phase III trial comparing pazopanib with sunitinib in patients with advanced clear cell renal cell carcinoma showed that although progression-free survival and overall survival were similar, pazopanib was better tolerated. Recent advances in genomics and metabolomics have provided novel insights that could be leveraged to improve therapy.